Sosialisasi dan Edukasi Penggunaan Aplikasi Presensi Berbasis Mobile Bagi Pegawai Non PNS di Lingkungan Puskesmas Kosambi untuk Meningkatkan Kedisiplinan Kerja - Adih Adih; Bagas Syahputra; Obay Sobarnas; Farlin Wabula; Valentino Liu; Ade Irma Nizar; Sukron Anggara; Muhammad Azhar Prasetyo; Fashya Mulya; Purnamasari Purnamasari; Abdullah Muhajir (Universitas 45 Surabaya, 2024)
This community service activity aims to improve the discipline and efficiency of non-civil servant employees at Kosambi Public Health Center (Puskesmas) through the implementation of a mobile attendance application. Currently, the manual attendance system used at Kosambi Puskesmas has numerous limitations, such as susceptibility to record errors, lack of transparency, and inability to monitor attendance in real time. To address this, socialization and educational activities were conducted on the use of the mobile attendance application, which is expected to enhance employees’ understanding and encourage attendance discipline. The methods used in this activity include socialization, discussion, and hands-on training. The results indicate that implementing this application can help improve discipline and transparency in managing employee attendance and has the potential to enhance the quality of healthcare services provided to the community at Kosambi Puskesmas.